Methods of effective organization of modern innovative teaching and learning processes (MMIT Proceedings, 2024)
The biggest challenge that every teacher faces in the modern education system is to attract the attention of students during the lesson and convey the knowledge they have learned in such a way that it will remain in their memory long after they leave the classroom. This requires implementing innovative ideas that redefine the classroom experience and make teaching methods more effective. This article explores some innovative ideas to help teachers reinvent their teaching methods and make their lessons more engaging. The use of innovative methods in educational institutions has the potential not only to improve education, but also to empower people, strengthen governance and strengthen efforts to achieve human development goals for the country. The purpose of this article is to suggest useful innovative teaching methods that can be easily imparted to students